ERROR ANALYSIS ON THE ARGUMENTATIVE ESSAYS WRITTEN BY THE FOURTH SEMESTER STUDENTS OF STUDY PROGRAM OF ENGLISH - YUWANTI, MAULIDA CAHYANING (Jurnal Ilmiah Mahasiswa FIB, 2014)
Yuwanti, Cahyaning, Maulida. 2014.  Error Analysis on the Argumentative Essays Written by the Fourth Semester Students of Study Program of English, Faculty of Cultural Studies Universitas Brawijaya. Study Program of English, Department of Languages and Literature Faculty of Cultural Studies Universitas Brawijaya. Supervisor: Endang Sasanti, Co – supervisor: Istiqomah Wulandari.Keywords: error analysis, surface strategy taxonomy.Error analysis is an analysis on error  in an essay of an essay in terms of grammar, verb omission, noun addition, etc. Almost every language learner who writes an essay makes error, so do the  fourth semester students of the English Department. In this study the researcher analyzed errors in the argumentative essays written by them and the problems were : 1) The errors found in the argumentative essay by the fourth semester students of English Department of Faculty of Cultural Studies of Brawijaya University. 2) The types of errors found in the argumentative essay by the fourth semester students of English Department Students of Faculty of Cultural Studies of Brawijaya University.  A qualitative approach was employed in this research. The data used by the researcher in this study were 30 students’ argumentative essays from the English Department, Faculty of Cultural Studies, Universitas Brawijaya in which the topic was decided by their lecturer. The data used were taken directly by the researcher from their class. All kinds of errors mentioned by Dulay in the surface strategy taxonomy were made by the students, but the researcher found that the error mostly made was misformation (Mf) with 127 errors (44%) especially misformation of “be”. Other mistakes made were omission (Om) with 95 errors (33%), then addition (Ad) with 57 errors (20%), and the last is misordering (Md) with 9 errors (3%).  It can be concluded that when producing a written work like an essay, the students focused on the content more than on grammar. Misformation errors were made the most because in Bahasa Indonesia as the L1, the structure like ‘be’ or regular and irregular past tense verbs are not significant or not found. Therefore, the students have to learn them as new knowledge. This needs time and it seems that studying them for four semesters is not enough. It is suggested that students give more time for studying grammar and its application.